Protocol for a randomized controlled dismantling study of a brief telephonic psychological intervention applied to non-professional caregivers with symptoms of depression - Vázquez, Fernando L. (BMC Psychiatry, 2015)
BACKGROUND: Although depression is a common problem in caregivers and there are effective cognitive-behavioral interventions for its prevention, the ability of caregivers to attend these treatments is often limited by logistics. Furthermore, the efficacy of the components of these interventions is unknown. The objectives of this study are to (a) evaluate the efficacy of a telephone-administered cognitive-behavioral intervention to prevent depression with all its components (cognitive and behavioral) and only with behavioral activation, and to (b) analyze the mediators of the change in depressive symptoms. METHODS/DESIGN: A randomized controlled clinical trial was designed to dismantle the components of a cognitive-behavioral intervention. Caregivers with elevated depressive symptoms will be randomly assigned to a cognitive-behavioral intervention, an intervention with only the behavioral activation component, or a usual care control group. Each condition will consist of approximately 60 participants. The two interventions will consist of five sessions lasting 90 min each, applied to groups of about 5 participants at a time via conference call. Trained interviewers, blind to the experimental conditions, will conduct the assessments at the pre-treatment, post-treatment and 1-, 3-, 6- and 12-month follow-ups. DISCUSSION: This study will provide evidence of the efficacy of a cognitive-behavioral intervention to prevent depression in caregivers with elevated depressive symptoms administered via conference call, and on the impact of the behavioral activation component on the overall efficacy of the program. If we find favorable results, it would mean that we have developed a program of prevention of depression of higher clinical utility and efficacy than those currently available, which would make it possible for a large number of caregivers to have access to such resources. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02292394. Registered 6 November 2014.